2016
DOI: 10.1007/s10865-016-9734-x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of factors associated with sexual risk taking among Black men who have sex with men: a comparison of younger and older populations

Abstract: Background In the United States, rates of human immunodeficiency virus (HIV) infection are highest among Black men who have sex with men (BMSM). Prior research indicates that younger BMSM in particular (i.e., BMSM 29 years of age and younger) are most at risk for HIV infection and that HIV incidence in this subpopulation has risen in recent years. It remains unclear, however, why younger BMSM, relative to BMSM 30 years of age and older, are at increased risk for HIV infection. Methods For the current study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…On the one hand are those that are young, educated, single, of low socioeconomic status and belonging to an LGBT association, and on the other hand are those who are older, with higher socioeconomic status, married to women and do not belong to any LGBT association. Similar to reports by Maskut and colleagues [28], we found that different factors impact on sexual behavior and risk practices of younger when compared with older MSM. Young MSM are more open about their sexual preferences, more likely to have multiple and concurrent male partners and rely on membership in LGBT associations for sexual networking as well as to obtain information about sexual health and well-being.…”
Section: Discussionsupporting
confidence: 90%
“…On the one hand are those that are young, educated, single, of low socioeconomic status and belonging to an LGBT association, and on the other hand are those who are older, with higher socioeconomic status, married to women and do not belong to any LGBT association. Similar to reports by Maskut and colleagues [28], we found that different factors impact on sexual behavior and risk practices of younger when compared with older MSM. Young MSM are more open about their sexual preferences, more likely to have multiple and concurrent male partners and rely on membership in LGBT associations for sexual networking as well as to obtain information about sexual health and well-being.…”
Section: Discussionsupporting
confidence: 90%
“…Findings from this study have implications for both future research as well as intervention development for HIV-positive YBMSM. The high rates of depression, social isolation and substance use behaviors seen in this study have been found in other work focused on YBMSM, including those who are HIV-positive [ 53 55 ]. These psychosocial conditions, particularly in combination are likely to have an additive impact on continuum of care outcomes for YBMSM.…”
Section: Discussionsupporting
confidence: 66%
“…Last, a 3-step approach was utilized to incorporate sociodemographic and behavioral factors into the optimal models. These factors included age, marital status (Not married = 1, engaged or married = 2, separated or divorced = 0), education, income, sexual identity (gay = 1, bisexual = 2, unsure = 0), number of male partners in the last 3 months, using a condom during the first sexual encounter with another man (Yes = 1, No = 0), having primary male partners (Yes = 1, No = 0), having casual male partners (Yes = 1, No = 0), and intervention group (crowdsourcing = 1, marketing = 0) (35)(36)(37)(38)(39). And then, categorical latent variable multinomial logistic regression was conducted with the identified class membership as an outcome variable and the aforementioned variables as predictors of class membership.…”
Section: Statistical Analysesmentioning
confidence: 99%